Eksistensi Tradisi Nyadran dalam Ketidakpastian Ekonomi Masyarakat Waruduwur Kabupaten Cirebon - Nurlaili Khikmawati (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
Indonesia is a region rich in ethnicity, culture and tradition. Every community has traditions that have been passed down from generation to generation, such as the nyadran tradition in coastal Java communities. One of the nyadran traditions in the coastal areas of Java is carried out by the people of Waruduwur, Cirebon. This research was conducted to examine how the Waruduwur people carry out the nyadran tradition in a famine economic condition. The data in this study were extracted using qualitative research methods with a brief ethnographic approach. The data collection method was carried out by interviews, observation, and documentation. The results showed that the Waruduwur people continued to carry out the nyadran tradition even though they were in a famine. Without reducing the sacredness of the tradition, the community made several adjustments, namely reducing the cost of the nyadran by not participating in the procession and reducing the ornaments carried during the nyadran procession. However, the nyadran is still carried out because it is considered to have sacred values and is able to bring goodness to people's lives in the future.